2022
DOI: 10.1021/acs.inorgchem.1c03088
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Transformation of Metal–Organic Framework Nanosheets into Oxygen Vacancy NixCo3–xO4 Arrays for Ultrahigh-Capacitance Supercapacitors with Long Lifespan

Abstract: The amino-functionalized bimetal NH2-NiCo-MOF nanosheet array is first fabricated on Ni foam substrates and then controllably transformed into oxygen vacancy bimetal oxide arrays by simply thermal annealing in air. This NiCo-based oxide array (Ni x Co3–x O4/NF) achieves high capacitance (2484 F g–1 at 1 A g–1), excellent rate performance (91.4%), and long cycling life when assessed as promising electrode material for supercapacitors. Notably, the existing oxygen vacancy in Ni x Co3–x O4 promotes the electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The ASC device renders an enhanced specific energy value of 68.9 W h kg –1 at a specific power of 1.28 kW kg –1 at a current density of 1 A g –1 . The E and P values of the NiCo 2 O 4 /MoSe 2 //AC device are superior to those of different ASC devices reported previously based on NiCo 2 O 4 and its composites such as NiCo 2 O 4 //AC (24.5 W h kg –1 and 175 W kg –1 ), NiCo 2 O 4 /carbon cloth//porous graphene paper [(32.9 W h kg –1 and 970.1 W kg –1 ), NiCo 2 O 4 /NiCoSe/nickel foam (NF)//AC (54.5 W h kg –1 and 350 W kg –1 ), NiCo 2 O 4 //AC cocoa-700 (47.7 W h kg –1 and 430 W kg –1 ), Ni x Co 3– x O 4 /NF//AC (39.3 W h kg –1 and 800.2 W kg –1 ), NiCo 2 O 4 –S@graphdiyne and AC (62.8 W h kg –1 and 747.9 W kg –1 ), Vo-NiCo 2 O 4 @carbon cloth-16 h//AC@C (43.6 W h kg –1 and of 281 W kg –1 ), and NiCo 2 O 4 –rGO//rGO (67.89 W h kg –1 and 1 kW kg –1 ) . The cyclic stability of the ASC device (Figure h) is examined up to continuous 10,000 GCD cycles at a current density of 30 A g –1 , and it withstands 95% of the initial capacitance at the end GCD cycle.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The ASC device renders an enhanced specific energy value of 68.9 W h kg –1 at a specific power of 1.28 kW kg –1 at a current density of 1 A g –1 . The E and P values of the NiCo 2 O 4 /MoSe 2 //AC device are superior to those of different ASC devices reported previously based on NiCo 2 O 4 and its composites such as NiCo 2 O 4 //AC (24.5 W h kg –1 and 175 W kg –1 ), NiCo 2 O 4 /carbon cloth//porous graphene paper [(32.9 W h kg –1 and 970.1 W kg –1 ), NiCo 2 O 4 /NiCoSe/nickel foam (NF)//AC (54.5 W h kg –1 and 350 W kg –1 ), NiCo 2 O 4 //AC cocoa-700 (47.7 W h kg –1 and 430 W kg –1 ), Ni x Co 3– x O 4 /NF//AC (39.3 W h kg –1 and 800.2 W kg –1 ), NiCo 2 O 4 –S@graphdiyne and AC (62.8 W h kg –1 and 747.9 W kg –1 ), Vo-NiCo 2 O 4 @carbon cloth-16 h//AC@C (43.6 W h kg –1 and of 281 W kg –1 ), and NiCo 2 O 4 –rGO//rGO (67.89 W h kg –1 and 1 kW kg –1 ) . The cyclic stability of the ASC device (Figure h) is examined up to continuous 10,000 GCD cycles at a current density of 30 A g –1 , and it withstands 95% of the initial capacitance at the end GCD cycle.…”
Section: Resultsmentioning
confidence: 56%
“…Moreover, nonnoble metals have drawn more interest for supercapacitors and CO 2 electro-reduction reactions. Single or mixed transition metal oxides with stoichiometric or non-stoichiometric structures have recently been paid more attention in energy storage 9 and electrocatalysis application 10 due to their excellent electrochemical properties, low cost, and eco-friendly nature. In this regard, spinel (AB 2 O 4 )-structured NiCo 2 O 4 was found to be a significant bifunctional material for supercapacitors and CO 2 electro-reduction reactions since it satisfies the aforementioned perquisites.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five elements, namely, C, N, O, Co, and Ni, are present on NiCo-MOF-3. The content of these elements varies with O, Co, and Ni predominating; nevertheless, all the five elements are evenly distributed on it, with no one location being particularly prominent and other locations loading tiny elements …”
Section: Resultsmentioning
confidence: 99%
“…The content of these elements varies with O, Co, and Ni predominating; nevertheless, all the five elements are evenly distributed on it, with no one location being particularly prominent and other locations loading tiny elements. 28 The N 2 adsorption−desorption isotherms and pore size distributions of NiCo-MOF-1/2/3/4 are demonstrated in Figure S1a−d. It is observed that all their adsorption− desorption isotherms are primely consistent with H3 hysteresis returns (type IV), proving their mesoporous laminar structures with commendable specific surface areas.…”
Section: Morphologies and Compositionsmentioning
confidence: 99%